Racism, homophobia, and the sexual health of young Black men who have sex with men in the United States: A systematic review. - Sarah E Janek; Lisvel A Matos; Sandy Hatoum; Marta I Mulawa; Leila Ledbetter; Michael V Relf (PLoS ONE)
Black gay, bisexual, and other men who have sex with men (BMSM) experience the highest rates of HIV acquisition annually out of any population in the United States, and young BMSM (YBMSM) are heavily impacted by this inequity as they enter adulthood. Despite a high annual HIV incidence, extant literature has found BMSM to engage in fewer sexual risk behaviors than White and Hispanic/Latino men who have sex with men, resulting in a gap between risk behaviors and the inequity of HIV infection. Structural factors, such as racism and homophobia, are thus being examined in order to understand this disconnect between behavior and HIV incidence. The purpose of this systematic review was to examine the discrimination experiences of YBMSM due to racism and homophobia in the United States and to evaluate the effect of these experiences on their sexual health. Four databases (MEDLINE, CINAHL Complete, APA PsycINFO, and Sociology Source Ultimate) were searched to examine the available qualitative, quantitative, and mixed method studies relevant to the research question. Out of 17 included studies, the majority were qualitative in design and were conducted in urban settings. Racism and homophobia affected YBMSM's sense of belonging, sexual identity, and sexual partnership choices. Often, masculinity would interact with these two constructs to impact how YBMSM engaged in sexual behavior, such as condomless sex, as well as their likelihood to seek sexual health care. Future research is needed to fully understand the relationships between discrimination and sexual health to develop effective structurally responsive interventions that will help decrease the inequities experienced by YBMSM.